Diagnosis and treatment of isolated autosomal recessive woolly hair/hypotrichosis - Xie, Ying; Luo, Sha; Yang, Yumei; Zou, Xin; Lv, Shuying; Du, Meijiao; Xu, Yonglong; Song, Xiaojuan; Qi, Changjie; Li, Nuo; Yang, Dingquan (Frontiers in Medicine, 2025)
Isolated autosomal recessive woolly hair/hypotrichosis (ARWH, OMIM:278150) is a rare congenital disorder marked by sparse, tightly curled “woolly” hair. ARWH is associated with mutations in LIPH, LPAR6/P2RY5, KRT25, and C3ORF52, with LIPH and LPAR6 as the primary causative genes. Mutation prevalence varies globally: in Japan, founder mutations c.736 T > A (p.Cys246Ser) and c.742C > A (p.His248Asn) in LIPH are predominant; Pakistan reports a recurrent LIPH exon 5 deletion (c.659_660del); Russia’s Volga-Ural region has an exon 4 deletion (c.527_628del); and 12 out of 19 Chinese ARWH cases are linked to LIPH c.742C > A. LPAR6 mutations are sporadic, with rare occurrences in Pakistani families and two Chinese cases. KRT25 mutations include the Russian founder variant c.712G > T (p.Val238Leu) and the Pakistani c.950 T > C (p.Leu317Pro). C3ORF52 mutations are newly identified and reported only in two U. S. cases. No definitive treatment exists, but minoxidil, gentamicin, regenerative therapies, and plant-derived compounds show potential. Regional mutation patterns highlight genetic founder effects and population-specific variations in ARWH pathogenesis.